2020
DOI: 10.3389/ffgc.2019.00087
|View full text |Cite
|
Sign up to set email alerts
|

Hunting and Forest Modification Have Distinct Defaunation Impacts on Tropical Mammals and Birds

Abstract: The mammalian and avian assemblages of intact tropical forests are among the most diverse vertebrate communities on Earth and influence the structure, composition, and functioning of these forests in myriad ways. Over recent centuries, however, increasing human domination of the tropics has led to widespread defaunation, or the decline, local-, or global extinction of tropical animal species. Defaunation is one of the defining features of the Anthropocene and is best documented for vertebrate species, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…2019; Osuri et al . 2020). Effective field‐based enforcement requires structured governance, significant financial resources and low corruption – conditions that are largely lacking in some developing countries (Börner et al .…”
Section: How Must Human Settlements and Infrastructure Be Managed?mentioning
confidence: 99%
“…2019; Osuri et al . 2020). Effective field‐based enforcement requires structured governance, significant financial resources and low corruption – conditions that are largely lacking in some developing countries (Börner et al .…”
Section: How Must Human Settlements and Infrastructure Be Managed?mentioning
confidence: 99%
“…Tropical rainforests are among the most biodiverse ecosystems in the world (Myers et al., 2000) and are the most threatened by habitat loss and fragmentation (Corlett, 2012; Davies et al., 2006). Threats to wildlife arise from land‐use change for food production, mineral extraction, urbanization, and expansion of transportation and energy infrastructure (Benítez‐López et al., 2010; Brooks et al., 2002), as well as from poaching, wildlife trade, and retaliatory killings (Osuri et al., 2020). Mitigation of these threats is often limited by financial constraints that force countries with developing economies to prioritize resources among several pressing issues.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications of the frugivore community (through logging or hunting of birds and terrestrial mammals) in the Neotropics have already been shown to reduce seed removal at the community level, leading to reduced plant recruitment and sapling density (Boissier et al, 2020). Similar effects can be expected for the Palaeotropics (Osuri et al, 2020), and it is crucial for such assessments to include pteropodids.…”
Section: Threats To the Ecological Roles Of Pteropodidsmentioning
confidence: 86%